1985
DOI: 10.1073/pnas.82.11.3834
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene C4 as a mediator of luteinizing hormone release from rat anterior pituitary cells.

Abstract: This study demonstrates that leukotriene C4, at concentrations in the picomolar range, released luteinizing hormone (LH) but not growth hormone (GH) from dispersed rat anterior pituitary cells. Leukotriene B4, another lipoxygenase pathway product of arachidonic acid, had no effect on LH or GH release. The stimulatory effect of leukotriene C4 could be seen after 0.5 but not after 3 hr of incubation. This was in contrast to the dose-dependent LH-releasing hormone (LHRH)-induced LH release that was not measurable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
3

Year Published

1986
1986
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 24 publications
3
34
0
3
Order By: Relevance
“…2 Tissues other than myeloid cell containing organs, such as the spleen and lymph nodes, that showed expression of the mRNA for the CysLT 2 receptor included regions of the central nervous system, the adrenal gland, and the heart. The synthesis and activities of cysteinyl leukotrienes in the brain of various animal species has been well documented (21)(22)(23). Studies on expression of both the CysLT 1 and CysLT 2 receptors in the central nervous system are under way in our laboratories.…”
Section: Human Tissue Rna Northern Blot and In Situ Analyses-mentioning
confidence: 99%
“…2 Tissues other than myeloid cell containing organs, such as the spleen and lymph nodes, that showed expression of the mRNA for the CysLT 2 receptor included regions of the central nervous system, the adrenal gland, and the heart. The synthesis and activities of cysteinyl leukotrienes in the brain of various animal species has been well documented (21)(22)(23). Studies on expression of both the CysLT 1 and CysLT 2 receptors in the central nervous system are under way in our laboratories.…”
Section: Human Tissue Rna Northern Blot and In Situ Analyses-mentioning
confidence: 99%
“…The 5-lipoxygenase pathway is of special interest because 5-HPETE and 5-HETE can be rapidly converted to leukotrienes, which are presumably the most active of the lipoxygenase metabolites of AA [ 13,141. It has been reported that leukotrienes are effective stimulators of LH release from dispersed rat anterior pituitary cells [9,10,15]. In view of the present demonstration of stimulatory effects of 5-HETE and 5-HPETE on P and PGE2 production, the role of leukotrienes on ovarian cell function warrants further investigation.…”
Section: Discussionmentioning
confidence: 68%
“…Two effectors might, however, result in generation of two different second messengers. Garcfa-Sainz and colleagues (14,15) [5] [HER] [HER-E2] Conservation of mass requires that Ho = H + H'R + H R E1 + H-R-E2 + 2H*R El R H + 2H-R-E2-R-H, [6] Ro= R + HER + HlR-El + HR'E2 + 2H R E1 R H + 2H*R-E2-R-H, [7] Elo = E1 + H-R-E1 + H-R*ElgR-H, [8] E2o = E2 + H-R-E2 + H-R*E2*R-H, [9] where H., R, E1o, and E20 are the total amounts (per unit volume) of ligand added, of receptor, of effector 1, and of effector 2, respectively. In Eqs.…”
mentioning
confidence: 99%
“…Leukotriene C4 (LTC4) has recently also been shown to stimulate LH release by anterior pituitary cells in primary culture (5). LH secretion is significantly increased with 1 fM LTC4, reaches a maximum at about 1 pM, and then decreases to near-basal levels as LTC4 concentration increases to 0.01…”
mentioning
confidence: 99%